2022
DOI: 10.3390/ijerph19095653
|View full text |Cite
|
Sign up to set email alerts
|

Partial Nitrification and Enhanced Biological Phosphorus Removal in a Sequencing Batch Reactor Treating High-Strength Wastewater

Abstract: Complex and high levels of various pollutants in high-strength wastewaters hinder efficient and stable biological nutrient removal. In this study, the changes in pollutant removal performance and microbial community structure in a laboratory-scale anaerobic/aerobic sequencing batch reactor (SBR) treating simulated pre-fermented high-strength wastewater were investigated under different influent loading conditions. The results showed that when the influent chemical oxygen demand (COD), total nitrogen (TN), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In the A 2 O reactor, the main genera were Acinetobacter (0.5%−28.7%), Lelliottia (0.3%−25.7%), and Competibacter (5.4%−19.3%), while Acinetobacter (12.0%−45.0%), Thiothrix (1.3%−23.2%) and Cloacibacterium (1.6%−9.3%) exhibited the highest abundance in SSH reactor. These dominant genera were commonly detected in previous BNR studies [8,46,57,58]. Competibacter, Thiothrix, and Cloacibacterium were known GAO, denitrifier and fermentative bacterium, respectively [59].…”
Section: Microbial Community Compositionmentioning
confidence: 75%
“…In the A 2 O reactor, the main genera were Acinetobacter (0.5%−28.7%), Lelliottia (0.3%−25.7%), and Competibacter (5.4%−19.3%), while Acinetobacter (12.0%−45.0%), Thiothrix (1.3%−23.2%) and Cloacibacterium (1.6%−9.3%) exhibited the highest abundance in SSH reactor. These dominant genera were commonly detected in previous BNR studies [8,46,57,58]. Competibacter, Thiothrix, and Cloacibacterium were known GAO, denitrifier and fermentative bacterium, respectively [59].…”
Section: Microbial Community Compositionmentioning
confidence: 75%
“…This behavior may be due to the influence of the high concentrations of COD and NH 4 -N in phases II and III, which, as found in the literature, are competitive against biological phosphorous removal. In fact, high organic loads favor the growth of non-polyphosphate-accumulating organisms and lead to polyphosphate-accumulating organisms being screened out of the system [56,57]. Our study found that the integrated anaerobic-aerobic MBBR and biochar adsorption method was highly effective in removing TP from landfill leachate, with a total maximum removal rate of 99.9%.…”
Section: Tp Removalmentioning
confidence: 75%